Sir Patrick Alfred Caldwell-Moore. 4 March 1923—9 December 2012. (28th December 2019) - May, Alex; Longair, Malcolm
Abstract : Patrick Moore was the archetype of the English eccentric, bringing a passionate enthusiasm for astronomy to the general public, principally through his long-running television series The Sky at Night . He was an inspired amateur who made no pretence at being a professional, but who had the extraordinary ability to communicate in simple, articulate and direct language the significance of advances in astronomy and astrophysics to the general public. He inspired generations of young people to take an interest in astronomy, and in science in general. This passion was combined with a love of everything English, especially cricket, and political views which might be mildly described as extreme right-wing.